2008
DOI: 10.1089/jwh.2007.0402
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Disparities in Time to Follow-Up after an Abnormal Mammogram

Abstract: Background: Although non-Hispanic white women have an increased risk of developing breast cancer, the disease-specific survival is lower for African American and Hispanic women. Little is known about disparities in follow-up after an abnormal mammogram. The goal of this study was to investigate potential disparities in follow-up after an abnormal mammogram. Methods: A retrospective cohort study of 6722 women with an abnormal mammogram and documented follow-up from January 2000 through December 2002 was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(120 citation statements)
references
References 49 publications
5
111
2
Order By: Relevance
“…In previous studies, lack of insurance was reported to delay follow-up care. 5,[20][21][22] Whereas low-income African American women in this study may have access to Medicaid, immigration status may impede eligibility for Latina women. Navigators enrolled women in Stand Against Cancer, a state program that finances cancer screenings and treatment for uninsured, low-income women regardless of immigration status.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In previous studies, lack of insurance was reported to delay follow-up care. 5,[20][21][22] Whereas low-income African American women in this study may have access to Medicaid, immigration status may impede eligibility for Latina women. Navigators enrolled women in Stand Against Cancer, a state program that finances cancer screenings and treatment for uninsured, low-income women regardless of immigration status.…”
Section: Discussionmentioning
confidence: 95%
“…4 These observed mortality and survival disparities are attributed to a number of factors, including delayed follow-up to abnormal cancer screening. 3,[5][6][7][8][9][10][11][12][13] Studies have reported individual factors associated with delays, including minority ethnicity; 5,11,[14][15][16][17][18][19] lack of health insurance or limitations of public insurance; 5,[20][21][22] younger age; 17,20,22 having less than a high school diploma; 18,23,24 and lack of regular access to a healthcare provider. 16 Medical-related factors associated with delay include absence of breast symptoms; 15,25 less severe test findings; 5,26 or previous abnormal test findings.…”
Section: Introductionmentioning
confidence: 99%
“…One national U.S. organization has undertaken to measure such timeliness as part of a quality assurance program ( 3 ) and is accumulating data, albeit using a self-selected group of reporting institutions. Reports are limited in regard to follow-up after screening, with most being issued from single institutions, some from regional data collection, and others reporting the effect of interventions in this process (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). We undertook this study because the current literature lacks a broad profi le of facility timeliness measures in regard to the additional evaluation of patients with screening-detected abnormalities.…”
Section: Breast Imaging: Timeliness Of Follow-up After Abnormal Screementioning
confidence: 99%
“…Latinas frequently experience delays in definitive diagnosis following an abnormal mammogram report (Ashing-Giwa, et al, 2010) (Chen, et al, 2010;Press, et al, 2008). They often do not understand what an abnormal mammogram means (Karliner, et al, 2005).…”
Section: Implications For Nursing Practicementioning
confidence: 99%
“…This percentage may be even greater among recent immigrants, and those with limited English skills and lower education levels. In particular, Hispanic ethnicity and low income have both been shown to be associated with longer wait times between the abnormal mammogram result and diagnostic follow-up compared to nonHispanic white women (n= 6000 women) (Press, Carrasquillo, Sciacca, & Giardina, 2008). Among a group of 11,000 low-income women enrolled in a free statewide screening program, a retrospective case-control analysis revealed that of the 37% that required follow-up, 30% experienced delays of more than 60 days and Hispanic and African-American women were more likely than Caucasians to experience delays (Wujcik et al, 2009).…”
mentioning
confidence: 99%